Low-Grade Dysplasia in Ulcerative Colitis: Risk Factors for Developing High-Grade Dysplasia or Colorectal Cancer - Choi, Chang-ho Ryan (Am J Gastroenterol, 2015)
OBJECTIVES: The aim of this study was to identify risk factors associated with development of high-grade dysplasia (HGD) or colorectal cancer (CRC) in ulcerative colitis (UC) patients diagnosed with low-grade dysplasia (LGD). METHODS: Patients with histologically confirmed extensive UC, who were diagnosed with LGD between 1993 and 2012 at St Mark's Hospital, were identified and followed up to 1 July 2013. Demographic, endoscopic, and histological data were collected and correlated with the development of HGD or CRC. RESULTS: A total of 172 patients were followed for a median of 48 months from the date of initial LGD diagnosis (interquartile range (IQR), 15–87 months). Overall, 33 patients developed HGD or CRC (19.1% of study population; 20 CRCs) during study period. Multivariate Cox proportional hazard analysis revealed that macroscopically non-polypoid (hazard ratio (HR), 8.6; 95% confidence interval (CI), 3.0–24.8; P<0.001) or invisible (HR, 4.1; 95% CI, 1.3–13.4; P=0.02) dysplasia, dysplastic lesions ≥1 cm in size (HR, 3.8; 95% CI, 1.5–13.4; P=0.01), and a previous history of “indefinite for dysplasia” (HR, 2.8; 95% CI, 1.2–6.5; P=0.01) were significant contributory factors for HGD or CRC development. Multifocal dysplasia (HR, 3.9; 95% CI, 1.9–7.8; P<0.001), metachronous dysplasia (HR, 3.5; 95% CI, 1.6–7.5; P=0.001), or a colonic stricture (HR, 7.4; 95% CI, 2.5–22.1; P<0.001) showed only univariate correlation to development of HGD or CRC. CONCLUSIONS: Lesions that are non-polypoid or endoscopically invisible, large (≥1 cm), or preceded by indefinite dysplasia are independent risk factors for developing HGD or CRC in UC patients diagnosed with LGD.